Perkembangan Tari Turak di Kabupaten Musi Rawas dan Kabupaten Rejang Lebong - Ira Miyarni Sustianingsih; Risa Marta Yati (Universitas Negeri Medan, 2020)
This study aims to describe and analyze the development of turak dance in Musi Rawas Regency, South Sumatra Province and Rejang Lebong Regency Bengkulu Province. The research method used is a qualitative method with a descriptive-analytical approach. The results of the study describe that turak dance is an authentic traditional dance originating from the Terawas area in Musi Rawas and Lembak districts in Rejang Lebong Regency. The name of this turak dance comes from turak which means bamboo. The bamboo weapon used as dance property during the independence war was filled with chillies with the aim of paralyzing the vision of Dutch soldiers who wanted to return to power. At present the development of turak dance in the two regencies is different, in which the creation of dance turak is mostly performed in the Musi Rawas area so that it gives birth to fan fan and scarf shawls. Meanwhile in Lembak, Rejang Lebong Regency, turak dance has not changed as in the Musi Rawas area.